Website of Trinity University of Asia - High School: An Interactive Platform for Prospective Students and Parents - Jamero, John Ervin R; Lee, Cheen-aij M; Manzon, Rofold Keen D; Mendoza, Ramon Issachar IV B; Reyes, Victoria M.; Crisostomo, Suzette C.; Villones, Roman B.; Bunag, Ferdinand R. (International Journal of Computing Sciences Research, 2024)
Purpose – The project aims to enhance the school's communication and information dissemination processes by providing a user-friendly and interactive platform for students, parents, and teachers. Method – The use of agile methodology in system development was essential because it allowed for adaptive planning, continuous feedback, and iterative development, enabling teams to respond to changing requirements and deliver high-quality software in a timely manner. Results – Achieving an excellent rating with a weighted mean of 4.5 for the website's Portability, Usability, and Reliability was extremely significant. It indicated that the website effectively met the needs and expectations of users in these crucial areas. Conclusion – It had a positive effect on the organization's online presence and user satisfaction. And underscored the website's success in meeting the organization's goals and user expectations, solidifying its reputation as a reliable and user-friendly platform. Recommendations – The development of the website provided the researchers with the opportunity to hone their skills and become proficient developers. They conducted research as a group and collaborated to improve the website, ultimately refining their concepts to create a user-friendly platform. Research Implications – The study allows to provide online information about school’s events, gives sufficient promotional and marketing activities, and increasingly the numbers of applicants to enroll in the school. The system has been implemented to aid Trinity University of Asia – High School and is updated and continuously maintained to its latest version. Practical Implications – Having information about the school on a website, creates an impact that can make a school known easily. And, to encourage students to enroll in the school by posting their offers to those students who are inquiring about the services they offer by looking at the internet.